Real time fabrication system for the design and fabrication of semiconductor lasers - Yu, Siu Fung. (2008)
The objective of this report is to develop a data processing/logging unit (the hardware, sub-unit of the fabrication system) for the characterizing of semiconductor lasers and a simulation program (the software) for the real time analysis and design of semiconductor lasers.